A visible-light-active CuInSe2:Zn/g-C3N4/TiO2 nanowires for photoelectrocatalytic bactericidal effects. (23rd January 2020) - Jiang, Ning; Geng, Hongchao; Qiao, Yan; Zhu, Xingqi; Li, Chenyi; Cai, Qingyun
Abstract : A visible-light-active CuInSe2 :Zn/g-C3 N4 /TiO2 nanowire (NW) photoelectrode was prepared by in situ growth of g-C3 N4 on the surface of TiO2 NWs, followed by drop deposition of Zn-doped CuInSe2 quantum dots (CuInSe2 :Zn QDs). Abstract : A visible-light-active CuInSe2 :Zn/g-C3 N4 /TiO2 nanowire (NW) photoelectrode was prepared by in situ growth of g-C3 N4 on the surface of TiO2 NWs, followed by drop deposition of Zn-doped CuInSe2 quantum dots (CuInSe2 :Zn QDs). It has a 2.205 eV band gap and can absorb visible light. The as-prepared ternary hybrid nanocomposite CuInSe2 :Zn/g-C3 N4 /TiO2 NWs shows high photon absorption and photocurrent generation efficiency, as well as a high bactericidal effect on Staphylococcus aureus .